The desert locust, Schistocerca gregaria, plastically manipulates egg size by regulating both egg numbers and production rate according to population density. (April 2020) - Maeno, Koutaro Ould; Piou, Cyril; Ghaout, Saïd
Graphical abstract: Highlights: Desert locusts show a density-dependent trade-off between egg size and number. Crowded females increased egg sizes and decreased clutch size. Crowded females prolonged oviposition interval. Abstract: Egg-size adjustment is one of the important plastic life-history traits for animals living in heterogeneous environments. The adaptive investment hypothesis predicts that mothers should increase progeny size according to certain cues predicting adverse future conditions of their offspring. However, reproductive resources are limited, and females have to simultaneously reduce egg number to allocate more resources to increase size. It remains unclear how single individuals alter egg size and number according to temporally heterogeneous environments. In the present study, we examined how desert locusts, Schistocerca gregaria, plastically alter egg size and number according to population density. We also investigated the trans-generational maternal effects on progeny characteristics as well as their own maternal physiological response (oviposition interval). Females kept in crowded conditions laid significantly larger and heavier eggs by reducing clutch size (number of eggs per egg pod) compared to isolated females, suggesting the existence of a reproductive trade-off between the two traits. The crowding-forced isolated females induced concerted changes not only in egg size but also in egg number tending towards those characteristics of gregarious control, implying that single individuals showed trade-off when egg size was increased. Double-blind testing confirmed the rapid crowding effects on egg size. Females also responded to crowding by extending the oviposition interval. As the oviposition interval extended, egg size increased, but clutch size decreased. Eggs from crowding-forced isolated females began to produce gregarious-phase type hatchlings (large and black) instead of solitarious-phase type ones (small and green). These results suggested that S. gregaria plastically manipulate egg size by regulating egg numbers and egg production rate, and indicated the presence of trans-generational maternal effects on progeny phase.